Method for preparing carbon composite material by implanting molecular catalyst into carbon carrier and application of carbon composite material
By introducing high-energy microwave irradiation into the liquid phase reaction system, the efficient solid support of molecular catalysts on the carbon support is achieved, and the problem of spontaneous agglomeration and electron transport of molecular catalysts in the carbon dioxide electroreduction reaction is solved, and efficient and stable carbon composite materials are prepared for carbon dioxide reduction reaction in electrolytic cells.
Patent Information
- Application Number
- CN202411725258.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, molecular catalysts have problems of spontaneous agglomeration accumulation and blockage of electron transport in the electroreduction reaction of carbon dioxide, which cannot meet the needs of electrically driven catalytic energy systems.
By introducing high-energy microwave irradiation physical field into the liquid phase reaction synthesis system, inducing the vaporization of the reaction medium, and building an in-situ liquid-solid phase transformation synthesis reaction system, achieving efficient solid support of molecular catalysts on carbon support.
This method can achieve high dispersion and strong immobility of molecular catalysts in a short time, and prepare carbon composite materials with excellent molecular catalyst implanted into carbon support. It has high catalytic activity, stable active substances and good selectivity, and is suitable for carbon dioxide reduction reaction in flow electrolytic cells.
Smart Images

Figure CN119506962A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon composite material by implanting a molecular catalyst into a carbon carrier and application thereof, belonging to the technical field of carbon composite material preparation. Background Art
[0002] Molecular catalysts with nitrogen-coordinated metal centers (e.g., metalloporphyrins and their derivatives) show extraordinary uniqueness and effectiveness in the electroreduction of carbon dioxide. However, the conjugated macrocyclic structure of the molecular catalyst itself easily promotes spontaneous aggregation and accumulation, masking the inherent active sites; in addition, the discontinuous conductive network between isolated catalyst units will also cause the problem of blocked electron transport, which cannot meet the needs of electrically driven catalytic energy systems. The high dispersion and strong immobilization of molecular catalysts can inhibit spontaneous aggregation, and the introduction of carbon carriers with long-range ordered conductive networks can strengthen the electron transfer path. The systematic coupling of the two is an effective way to solve the above problems.
[0003] Solid-phase reaction and liquid-phase reaction are commonly used methods for immobilizing molecular catalysts on carbon carriers. The solid-phase reaction technology route represented by traditional pyrolysis and high-energy ball milling uses the energy generated by high-temperature environment or high-speed collision to anchor the molecular catalyst on the carbon carrier, and can obtain solid catalyst powder and directly use it for catalytic reaction. However, the single solid-phase synthesis process has the disadvantages of insufficient reaction, poor local physical properties, and easy sintering / aggregation of metal components. In addition, the liquid-phase reaction technology route represented by chemical grafting and π-π composite method realizes the connection / composite of molecular catalyst and carbon carrier through chemical reaction or physical adsorption between precursor components dispersed in an appropriate liquid reaction medium, which has the advantages of sufficient component contact, stable reaction environment, and good product uniformity. However, the liquid-phase reaction process involves cumbersome chemical reaction steps and is extremely dependent on precise molecular assembly reactions. At the same time, the separation of target products is a major challenge.
[0004] Based on this, the present invention proposes to introduce a high-energy microwave irradiation physical external field into the liquid phase reaction synthesis system, which can induce the vaporization of the reaction medium in a short time to construct a synthetic reaction system with an in-situ liquid-solid phase transition function, thereby realizing the efficient immobilization of molecular catalysts on carbon carriers without the need for additional product separation steps. Specifically, in the initial stage of the reaction, the liquid phase chemical medium (such as nitrogen-containing substances) can be used as an effective promoter and microwave absorber for the generation of defects to ensure the construction of abundant defect sites on the carbon substrate for anchoring molecular catalysts; subsequently, the microwave physical field gives continuous and intensive energy input to rapidly increase the temperature of the reaction system, the liquid phase reaction medium gradually vaporizes, and the solid phase substance absorbs energy as a microwave absorption medium, further strengthening the interaction between the molecular catalyst and the carbon carrier. Therefore, this in-situ liquid-solid phase transition has the advantages of a single solid phase or liquid phase reaction. The reasonably matched high-energy physical field and liquid phase chemical medium can construct defect structures on the surface of the carbon carrier as anchoring points, and realize the implantation process of the molecular catalyst in the carbon carrier skeleton surface on a minute time scale, thereby ensuring the high dispersion and strong fixation of the active sites carried by the molecular catalyst unit on the carbon carrier. Summary of the invention
[0005] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a carbon composite material by implanting a molecular catalyst into a carbon carrier and its application. The method uses the in-situ liquid-solid phase transition of a nitrogen-containing liquid chemical medium induced by a high-energy microwave physical external field to construct defects on the surface of the carbon material, and then accurately disperses and immobilizes the molecular catalyst on a conductive carbon substrate. The process is simple, the operation cycle is short, and the integrated efficiency is high. A solid catalyst can be directly obtained in a one-pot reaction without the need for post-processing processes such as separation and drying, and the precise synthesis of highly active carbon composite catalytic materials under low energy consumption conditions can be achieved. The carbon composite material with a molecular catalyst implanted into a carbon carrier prepared by this method has a compact spatial structure. The molecular catalyst is implanted into the carbon carrier skeleton, which can maximize the inherent activity of the molecular catalyst. It has the advantages of high catalytic activity, stable active substances, high selectivity, etc., and has great application potential in the field of catalysis. On this basis, the catalytic activity of the material in the carbon dioxide reduction reaction in a flow-type electrolytic cell is explored.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is: a method for preparing a carbon composite material by implanting a molecular catalyst into a carbon carrier, comprising the following steps:
[0007] Step 1, measuring a liquid nitrogen-containing medium with a volume of 5-20 mL, transferring the solution to a homemade quartz tube reactor with a size unit of cm, an aspect ratio of 29:2.5, and an air outlet on the outside, weighing 2-50 mg of a molecular catalyst and 50-100 mg of a conductive carbon carrier, mixing them evenly and transferring them to the quartz tube reactor; then placing the quartz tube reactor containing the reaction reagent in an ultrasonic instrument for 30-60 min to obtain a uniformly mixed suspension; the liquid nitrogen-containing medium is selected from one of formamide, dimethylformamide, ammonia water, acetonitrile or ethylenediamine, the molecular catalyst is selected from one of tetraphenylporphyrin iron, tetra-p-tolylporphyrin iron, tetraphenylporphyrin copper, cobalt protoporphyrin IX chloride, chloroprotoporphyrin IX iron (III), o-phenanthroline iron or o-phenanthroline nickel, and the conductive carbon carrier is selected from one of carbon nanotubes, graphene or graphene oxide;
[0008] Step 2, placing the quartz tube reactor containing the suspension obtained in step 1 in a microwave electromagnetic field and fixing it, introducing a continuous flow of argon or nitrogen from the upper tube port for 30-60 min to fully replace the air inside the quartz tube reactor, continuing to maintain the introduction of flowing argon or nitrogen as a protective gas, and performing a synthesis reaction at a microwave power of 700-900 W. The synthesis reaction adopts liquid-solid two-stage microwave irradiation. The first stage is a liquid phase microwave irradiation stage, which ends when the microwave radiation switch is turned on to generate steam inside the quartz tube reactor and the nitrogen-containing medium is completely vaporized and escaped; the second stage is a solid phase microwave irradiation stage, using a countdown reaction mode, and the microwave irradiation time in this stage is set to 1-15 min. The solid inside the quartz tube reactor is used as a microwave absorption medium, and a washing bottle is connected to the gas outlet to recover and process the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas. After the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, and the generated solid catalyst is collected to obtain a carbon composite material with a molecular catalyst implanted in a carbon carrier.
[0009] The carbon composite material in which the molecular catalyst prepared by the method is implanted into a carbon carrier is used as an electrode active material in a flow-type electrolytic cell to implement a carbon dioxide electrochemical reduction catalytic reaction.
[0010] The beneficial effects of the present invention are: a method for preparing a carbon composite material by implanting a molecular catalyst into a carbon carrier and its application, wherein the preparation method comprises the following steps: (1) uniformly mixing a liquid nitrogen-containing medium, a molecular catalyst and a conductive carbon carrier and transferring the mixture to a quartz tube reactor, and then placing the quartz tube reactor containing the reaction reagent in an ultrasonic instrument for treatment to obtain a uniformly mixed suspension; (2) placing the quartz tube reactor containing the suspension obtained in step 1 in a microwave electromagnetic field for liquid-solid two-stage microwave irradiation, and after the reaction is completed, continuing to introduce argon or nitrogen until the quartz tube reactor is cooled to room temperature, collecting the generated solid catalyst, and preparing a carbon composite material with a molecular catalyst implanted into a carbon carrier. The method of the present invention has a simple process route, a short operation cycle, high integration efficiency, and low process energy consumption. The solid catalyst can be directly obtained in a one-pot reaction through an in-situ liquid-solid phase transition, without the need for post-processing processes such as separation and drying, and can effectively construct defects on the conductive carbon carrier to immobilize and integrate the molecular catalyst into the conductive carbon substrate skeleton, thereby preparing a carbon composite material with a molecular catalyst implanted into a carbon carrier with excellent performance. The carbon composite material prepared by the method and implanted with a molecular catalyst into a carbon carrier has a compact spatial structure, and the molecular catalyst is implanted inside the carbon carrier skeleton. The method is used to prepare a carbon composite catalyst, and the catalyst yield can be maintained at more than 95%. The composite material has the advantages of high catalytic activity, stable active substances, and high selectivity, and has great application potential in the field of catalysis. On this basis, the catalytic activity of the composite material in the carbon dioxide reduction reaction in a flow-type electrolytic cell was investigated, and the Faraday efficiency of the reduced product carbon monoxide was between 50 and 300 mA cm –2 The current density range is maintained above 90%. At the same time, at an overpotential of 1.06 V, it exhibits an excellent unit site turnover frequency (TOF), with a TOF value of up to 241,000 h –1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is the X-ray absorption spectrum of the target material prepared in Example 2.
[0012] Among them: (a) is the X-ray near-edge absorption structure spectrum, and (b) is the extended X-ray absorption fine structure spectrum.
[0013] Figure 2 This is the infrared spectrum test chart of the target material prepared in Example 7.
[0014] Figure 3 is a graph of the Faraday efficiency of the electrochemical reduction of carbon dioxide described in Example 9.
[0015] Figure 4 This is the unit site turnover frequency (TOF) graph described in Example 9. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the embodiments.
[0017] Example 1
[0018] Measure 20 mL of acetonitrile, transfer the solution to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5, and an air outlet on the outside, weigh 50 mg of nickel-1-phenanthroline and 50 mg of graphene, mix them evenly, and transfer them to the quartz tube reactor; then place the quartz tube reactor containing the reaction reagents in an ultrasonic instrument for 30 min to obtain a uniformly mixed suspension; place the obtained quartz tube reactor containing the suspension in a microwave electromagnetic field and fix it, and continuously flow argon or nitrogen from the upper tube port for 30 min to fully replace the air inside the quartz tube reactor, continue to keep flowing argon or nitrogen as a protective gas, and heat at 700 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 5 min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 96 mg, and the yield is 96.0%.
[0019] Example 2
[0020] 5 mL of dimethylformamide was measured and the solution was transferred to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5 and an air outlet on the outside. 2 mg of chloroprotoporphyrin IX iron (III) and 100 mg of carbon nanotubes were weighed, mixed evenly and transferred to the quartz tube reactor. The quartz tube reactor containing the reaction reagents was then placed in an ultrasonic instrument for 60 min to obtain a uniformly mixed suspension. The obtained quartz tube reactor containing the suspension was fixed in a microwave electromagnetic field, and argon or nitrogen was continuously flowed from the upper tube port for 60 min to fully replace the air inside the quartz tube reactor. The flowing argon or nitrogen was continued to be introduced as a protective gas at 900 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, the nitrogen-containing medium is completely vaporized and escaped; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 10min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid temperature rise and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 100 mg, and the yield is 98.0%. Its X-ray absorption spectrum, such as Figure 1 As shown, the coordination configuration of the metal sites originally attributed to the molecular catalyst in the obtained material is retained, proving that the molecular catalyst is successfully immobilized on the carbon support.
[0021] Example 3
[0022] 15 mL of ammonia water was measured and the solution was transferred to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5 and an air outlet on the outside. 20 mg of o-phenanthroline iron and 80 mg of graphene oxide were weighed, mixed evenly and transferred to the quartz tube reactor. The quartz tube reactor containing the reaction reagents was then placed in an ultrasonic instrument for 60 min to obtain a uniformly mixed suspension. The obtained quartz tube reactor containing the suspension was fixed in a microwave electromagnetic field, and argon or nitrogen was continuously flowed from the upper tube port for 60 min to fully replace the air inside the quartz tube reactor. The flowing argon or nitrogen was continued to be introduced as a protective gas at 900 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 10min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 99 mg, and the yield is 99.0%.
[0023] Example 4
[0024] Measure 20 mL of formamide, transfer the solution to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5, and an air outlet on the outside, weigh 5 mg of cobalt protoporphyrin IX chloride and 100 mg of carbon nanotubes, mix them evenly, and then transfer them to the quartz tube reactor; then place the quartz tube reactor containing the reaction reagents in an ultrasonic instrument for 60 min to obtain a uniformly mixed suspension; place the obtained quartz tube reactor containing the suspension in a microwave electromagnetic field and fix it, and continuously flow argon or nitrogen from the upper tube port for 60 min to fully replace the air inside the quartz tube reactor, continue to keep flowing argon or nitrogen as a protective gas, and heat it at 900 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 10min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 102 mg, and the yield is 97.1%.
[0025] Example 5
[0026] 5 mL of ethylenediamine was measured and the solution was transferred to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5 and an air outlet on the outside. 5 mg of tetraphenylporphyrin copper and 100 mg of graphene were weighed, mixed evenly and transferred to the quartz tube reactor. The quartz tube reactor containing the reaction reagents was then placed in an ultrasonic instrument for 30 min to obtain a uniformly mixed suspension. The obtained quartz tube reactor containing the suspension was fixed in a microwave electromagnetic field, and argon or nitrogen was continuously flowed from the upper tube port for 50 min to fully replace the air inside the quartz tube reactor. The flowing argon or nitrogen was continued to be introduced as a protective gas at 800 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 12min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 100 mg, and the yield is 95.2%.
[0027] Example 6
[0028] 5 mL of dimethylformamide was measured and the solution was transferred to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5 and an air outlet on the outside. 4 mg of tetraphenylporphyrin iron and 100 mg of carbon nanotubes were weighed, mixed evenly and transferred to the quartz tube reactor. The quartz tube reactor containing the reaction reagents was then placed in an ultrasonic instrument for 30 min to obtain a uniformly mixed suspension. The obtained quartz tube reactor containing the suspension was fixed in a microwave electromagnetic field, and argon or nitrogen was continuously flowed from the upper tube port for 30 min to fully replace the air inside the quartz tube reactor. The flowing argon or nitrogen was continued to be introduced as a protective gas at 900 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 10min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 101 mg, and the yield is 97.1%.
[0029] Example 7
[0030] 5 mL of dimethylformamide was measured and the solution was transferred to a self-made quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5 and an air outlet on the outside. 3 mg of chloroprotoporphyrin IX iron (III) and 50 mg of carbon nanotubes were weighed, mixed evenly and transferred to the quartz tube reactor. The quartz tube reactor containing the reaction reagents was then placed in an ultrasonic instrument for 30 min to obtain a uniformly mixed suspension. The obtained quartz tube reactor containing the suspension was fixed in a microwave electromagnetic field, and argon or nitrogen was continuously flowed from the upper tube port for 30 min to fully replace the air inside the quartz tube reactor. The flowing argon or nitrogen was continued to be introduced as a protective gas at 900 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 8min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid temperature rise vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 51 mg, and the yield is 96.2%. Infrared spectrum test chart, such as Figure 2 shown.
[0031] Example 8
[0032] 15 mL of formamide was measured and the solution was transferred to a homemade quartz tube reactor with a size unit of cm, a length-to-diameter ratio of 29:2.5 and an air outlet on the outside. 5 mg of tetra-p-tolylporphyrin iron and 100 mg of carbon nanotubes were weighed, mixed evenly and transferred to the quartz tube reactor. The quartz tube reactor containing the reaction reagents was then placed in an ultrasonic instrument for 30 min to obtain a uniformly mixed suspension. The obtained quartz tube reactor containing the suspension was fixed in a microwave electromagnetic field, and argon or nitrogen was continuously flowed from the upper tube port for 30 min to fully replace the air inside the quartz tube reactor. The flowing argon or nitrogen was continued to be introduced as a protective gas at 900 °C. W microwave power for synthesis reaction, the synthesis reaction adopts liquid-solid two-stage microwave irradiation, the first stage is the liquid phase microwave irradiation stage, from turning on the microwave radiation switch to generating steam inside the quartz tube reactor, and ending when the nitrogen-containing medium is completely vaporized and escapes; the second stage is the solid phase microwave irradiation stage, using the countdown reaction mode, the microwave irradiation time of this stage is set to 15min, the solid inside the quartz tube reactor is used as the microwave absorption medium, the gas outlet is connected to the washing bottle, the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas is recovered and processed, after the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, the generated solid catalyst is collected, and the carbon composite material with molecular catalyst implanted in the carbon carrier is obtained, the mass is 103 mg, and the yield is 98.1%.
[0033] Example 9
[0034] The prepared carbon composite material with molecular catalyst implanted in carbon carrier was tested for its performance of electrochemical reduction of carbon dioxide. The electrochemical workstation used was Shanghai Chenhua CHI 1140C. In the flow-type electrolytic cell, 1 M KHCO3 solution was used as the electrolyte, Ag / AgCl electrode was used as the reference electrode, nickel foam was used as the counter electrode, and the gas diffusion electrode with the carbon composite material with molecular catalyst implanted in carbon carrier was used as the working electrode to form a three-electrode system. Specifically, 4 mg of the carbon composite material with molecular catalyst implanted in carbon carrier prepared in Example 2 was weighed and dissolved in 970 μL of ethanol, and then 30 μL of Nafion binder was added. After ultrasonic treatment for 30 min, it was drop-coated on 1 cm 2 The operation was repeated until the molecular catalyst was implanted into the carbon composite material with a loading of 0.5 mg cm –2 The carbon composite material with molecular catalyst implanted into the carbon carrier exhibited excellent catalytic performance, and the Faraday efficiency of the reduced product carbon monoxide was between 50 and 300 mA cm –2 The current density range is maintained above 90%. The Faraday efficiency diagram of carbon dioxide electrochemical reduction is shown in Figure 3At the same time, at an overpotential of 1.06 V, it exhibits an excellent unit site turnover frequency (TOF), with a TOF value of up to 241,000 h –1 , the unit point turnover frequency (TOF) diagram, such as Figure 4 shown.
Claims
1. A method for preparing a carbon composite material by implanting a molecular catalyst into a carbon carrier, characterized in that: The following steps are involved: Step 1, measuring a liquid nitrogen-containing medium with a volume of 5-20 mL, transferring the solution to a homemade quartz tube reactor with a size unit of cm, an aspect ratio of 29:2.5, and an air outlet on the outside, weighing 2-50 mg of a molecular catalyst and 50-100 mg of a conductive carbon carrier, mixing them evenly and transferring them to the quartz tube reactor; then placing the quartz tube reactor containing the reaction reagent in an ultrasonic instrument for 30-60 min to obtain a uniformly mixed suspension; the liquid nitrogen-containing medium is selected from one of formamide, dimethylformamide, ammonia water, acetonitrile or ethylenediamine, the molecular catalyst is selected from one of tetraphenylporphyrin iron, tetra-p-tolylporphyrin iron, tetraphenylporphyrin copper, cobalt protoporphyrin IX chloride, chloroprotoporphyrin IX iron (III), o-phenanthroline iron or o-phenanthroline nickel, and the conductive carbon carrier is selected from one of carbon nanotubes, graphene or graphene oxide; Step 2, placing the quartz tube reactor containing the suspension obtained in step 1 in a microwave electromagnetic field and fixing it, introducing a continuous flow of argon or nitrogen from the upper tube port for 30-60 min to fully replace the air inside the quartz tube reactor, continuing to maintain the introduction of flowing argon or nitrogen as a protective gas, and performing a synthesis reaction at a microwave power of 700-900 W. The synthesis reaction adopts liquid-solid two-stage microwave irradiation. The first stage is a liquid phase microwave irradiation stage, which ends when the microwave radiation switch is turned on to generate steam inside the quartz tube reactor and the nitrogen-containing medium is completely vaporized and escaped; the second stage is a solid phase microwave irradiation stage, using a countdown reaction mode, and the microwave irradiation time in this stage is set to 1-15 min. The solid inside the quartz tube reactor is used as a microwave absorption medium, and a washing bottle is connected to the gas outlet to recover and process the nitrogen-containing medium vapor generated by the rapid heating and vaporization entrained by the protective gas. After the reaction is completed, argon or nitrogen is continued to be introduced until the quartz tube reactor is cooled to room temperature, and the generated solid catalyst is collected to obtain a carbon composite material with a molecular catalyst implanted in a carbon carrier.
2. The carbon composite material prepared by the method according to claim 1 and implanted with a carbon carrier as an electrode active material is used in a flow-type electrolytic cell to implement an electrochemical reduction catalytic reaction of carbon dioxide.